Determinants of Manufacturing Firms’ Financial Performance in Pakistan - DR. SAID SHAH; S.M. AMIR SHAH (Journal of Business & Tourism, 2021)
Investment in working capital by and large shows better returns than investment in fixed assets. As such proper management of working capital rightfully attracts a lot of attention. The objective of this research is to examine the impact of size and working capital management efficiency on firms’ financial performance using 10 years (2004- 2013) secondary data of 153 firms listed on Pakistan Stock Exchange and employing regression and ratio analyses. Results show that performance-wise large firms are better whereas WCME-wise small and medium firms are better. These findings indicate that better performance of large firms is not because of efficient utilization of working capital - rather it may be due to some other factors and these firms can further improve their performance if working capital is managed more efficiently.